Translation and psychometrical properties of Coronavirus Anxiety Scale (CAS) in Peruvian young people and adults - Franco-Jimenez, Rulman Andrei (2020)
Background: The overall aim of the study was to translate into Spanish and evaluate the psychometric properties of the Coronavirus Anxiety Scale (CAS). Method: The sample was composed of 622 Peruvian young people and adults who answered CAS. The structural evaluation was conducted with confirmatory factor analysis. Factorial invariance was used to verify the equivalence by sex and age. Results: The unifactorial model revealed good fit indexes χ²(5) = 12.40, CFI = .998, TLI = .996, RMSEA = .049, SRMR = .033.  Also, the internal consistency using McDonald´s Omega coefficient was high (ω > .80). The factorial invariance indicated that the unifactorial structure is stable according to age. Conclusion: The Peruvian version of the CAS has evidence to be considered an accurate, valid, and invariant measure and the results support the unifactorial model.